2008
DOI: 10.1093/ajcn/88.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil intake compared with olive oil intake in late pregnancy and asthma in the offspring: 16 y of registry-based follow-up from a randomized controlled trial

Abstract: Under the assumption that intake of olive oil in the dose provided here was inert, our results support that increasing n-3 PUFAs in late pregnancy may carry an important prophylactic potential in relation to offspring asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
189
2
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 42 publications
3
189
2
10
Order By: Relevance
“…It was estimated that 30% of children in the placebo group would have allergies, which was conservative given that this follow-up study includes children with both single and double familial risk. Similarly, the postulated effect size of a 40% relative reduction in allergic disease was modest and realistic compared with the 67% and 59% relative reductions in child allergy outcomes reported by Furuhjelm et al 8 and Olsen et al, 16 respectively, in response to fish oil treatment during pregnancy. All analyses were performed according to the intention to treat principle.…”
Section: Sample Size and Satistical Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…It was estimated that 30% of children in the placebo group would have allergies, which was conservative given that this follow-up study includes children with both single and double familial risk. Similarly, the postulated effect size of a 40% relative reduction in allergic disease was modest and realistic compared with the 67% and 59% relative reductions in child allergy outcomes reported by Furuhjelm et al 8 and Olsen et al, 16 respectively, in response to fish oil treatment during pregnancy. All analyses were performed according to the intention to treat principle.…”
Section: Sample Size and Satistical Analysismentioning
confidence: 79%
“…[9][10][11][12][13][14] However, these observational studies are unable to establish causality because of the difficulty in adjusting for complex confounding factors. 15 Randomized controlled trials (RCTs) of n-3 LCPUFA supplementation during pregnancy have reported protective effects; however, apart from 1 16-year registry based follow-up, 16 all reported allergic disease outcomes are in early childhood (between 1 and 3 years of age). 7,8,[17][18][19][20] In addition, the small sample size of a number of RCTs 7,8,19,20 introduces bias and a degree of uncertainty regarding results.…”
mentioning
confidence: 99%
“…These observations are in contrast to results from previous studies, which mainly, but not consistent, suggest that maternal fish intake during pregnancy protects against the development of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Observational studies in large cohorts observed lower incidence of eczema in offspring of mothers with the highest fish consumption during pregnancy, 19,21 but not lower incidences of wheezing or asthma. In the Netherlands, fish consumption is relatively low, which can explain the differences in the observations.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
“…7 Many observational and interventional studies, explored the associations of maternal fish consumption or fish oil supplementation during pregnancy with the risks of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although these studies showed a protective effect on at least one outcome, they were not all able to adjust for potential confounders. Also, previous intervention studies differed in selection of participants, types of intervention and definition of outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, although some authors report an association between the intake of lipids, certain fatty acids and certain foods and asthma (Bolte et al, 2005;Laerum et al, 2007;Olsen et al, 2008), others have found none (Devereux and Seaton, 2005;Almqvist et al, 2007;Kim et al, 2009;de Vries and Howie, 2009). Nevertheless, because of the fact that saturated fatty acids (SFAs) intake among children is very high nowadays, reaching the double of the recommended intake in some cases (Royo-Bordonada et al, 2006;McNeill et al, 2010), SFAs intake could be related to the increase in the prevalence of asthma.…”
Section: Introductionmentioning
confidence: 99%